Upregulation of TTYH3 promotes epithelial-to-mesenchymal transition through Wnt/β-catenin signaling and inhibits apoptosis in cholangiocarcinoma - Xue, Weijie; Dong, Bingzi; Zhao, Yanjie; Wang, Yixiu; Yang, Chenyu; Xie, Yuwei; Niu, Zhaojian; Zhu, Chengzhan (Cellular oncology (Dordrecht), 2021)
Purpose Cholangiocarcinoma (CCA) is a highly invasive malignant tumor originating from the bile duct epithelium. Tweety homolog 3 (TTYH3) is a member of the family of calcium-activated chloride channels, which have several biological functions. Here, we aimed to investigate the expression and biological function of TTYH3 in CCA. Methods The mRNA and protein expression levels of TTYH3 were investigated in primary human CCA tissues and normal tissues. The DNA methylation levels of three CpG sites in the TTYH3 promoter region were evaluated using pyrosequencing. The effect of TTYH3 expression on proliferation, apoptosis, migration and invasion were assessed in HUCCT1 and QBC939 cells. Xenograft models were developed to substantiate its role in the development of CCA. Western blot analysis was used to investigate the mechanistic role of TTYH3 in regulating CCA progression. Results We found that TTYH3 was highly expressed both at the mRNA and protein levels in CCA ( p = 0.0001) and that the expression levels were significantly related to a poor overall survival of the patients ( p = 0.0019). The DNA methylation levels of three CpG sites in the TTYH3 promoter region were significantly lower in CCA tissues compared to normal tissues ( p < 0.05). In vitro studies indicated that TTYH3 can promote the proliferation, migration and invasion of the CCA cells. TTYH3 overexpression significantly promoted tumor progression and cellular proliferation in vivo as indicated by Ki‐67 expression. In addition, we found that exogenous TTYH3 overexpression induced epithelial-mesenchymal transition (EMT) in CCA as indicated by expression changes in E-cadherin, N-cadherin and vimentin. The EMT process was found to occur through the Wnt/β-catenin signaling pathway, with simultaneous changes in P-GSK3β and β-catenin levels. Conclusions Our data indicate that DNA hypomethylation-induced overexpression of TTYH3 regulates CCA development and metastasis through the Wnt/β-catenin pathway.